Tunable mesoscale-structured self-assembled hydrogels synthesized by organocatalytic ring-opening polymerization. (18th May 2015) - Fox, Courtney H.; Engler, Amanda C.; Toney, Michael F.; Hedrick, James L.; Frank, Curtis W.
Abstract: A class of tunable, mesostructured self-assembled hydrogels has been developed based on a library of π–π stacking ABA-type telechelic triblock copolymers prepared by organocatalytic ring-opening polymerization (ROP). Poly(ethylene glycol) (PEG) served as a macroinitiator for ROP of methylene tricarbonate-benzyl ester (MTC-OBn), a benzyl-ester functionalized cyclic carbonate monomer, resulting in polymers with well-defined length and narrow polydispersity. Self-assembled hydrogels were formed by dissolving poly(MTC-OBn)- b -PEG- b- poly(MTC-OBn) copolymers in water. Physical cross-links in the hydrogels formed through hydrophobic and π–π stacking intermolecular interactions between poly(MTC-OBn) segments. The mesoscale material properties were probed using small angle X-ray scattering (SAXS) and dynamic mechanical measurements. SAXS spectra show a scattering peak, corresponding to a molecular domain spacing of 20–25 nm, which we attribute to the formation of electron-dense poly(MTC-OBn) assemblies. Results from oscillatory shear experiments were analyzed in conjunction with SAXS data in order to develop an understanding of the influence that nanoscale structure has on the mechanical properties of self-assembled gels. Modeling of scattering peaks using the Bragg spacing model demonstrated that the hydrophilic PEG network chains connecting the scattering moieties behaved as a two-dimensional self-avoiding walk. We compared the observed microstructural features with the mechanical properties of self-assembled gels and determined that the molecular weight of the polycarbonate and PEG segments controls the gel structure on both the mesoscale and macroscale. A central contribution of this work is a synthetic strategy that utilizes ROP to control polymer structure, which in turn controls both the structure and mechanical properties of these biodegradable self-assembled hydrogels. Graphical abstract: Highlights: Ring-opening polymerization (ROP) gives elegant control over polymer synthesis. SAXS gives a clear understanding of the microstructure of soft materials. The length of the components of triblock copolymers controls the gel structure and properties. ROP can be used to influence the microstructure and mechanical properties of hydrogels.